Pengujian Asap Cair Tempurung Kelapa Dalam Mengendalikan Patogen Colletotrichum gloeosporioides Penyebab Penyakit Antraknosa Pada Cabai (Capsicum annum L.) - Naufal, Sari M; Rumahlewang, Wilhelmina; Tuhumury, Gratiana N C (Jurnal Agrosilvopasture-Tech, 2023)
Colletotrichum gloeosporioides is a type of pathogen that causes anthracnose. This disease is classified as a major disease in chili plants which can cause great losses. Liquid smoke contains antimicrobial compounds such as phenols and acids which effectively kill and inhibit pathogenic fungi. This study aims to determine the effectiveness of coconut shell liquid smoke in controlling Colletotrichum gloeosporioides which causes anthracnose disease in chili plants. The variables in this study included the macroscopic and microscopic characteristics of the fungi, the diameter of the colony and the effectiveness of the inhibition. This study used liquid smoke types A3 (grade 3 liquid smoke self-made) A1 (grade 1 liquid smoke sold commercially) and A2 (grade 2 liquid smoke sold commercially) with different dose levels, namely, D1 (0.5 ml ), D2 (1 ml) and D3 (1.5 ml). The results of this study showed that coconut shell of A3 was effective in controlling C. gloeosporioides at treatment dose of 1 ml for each type of liquid smoke with an inhibition percentage 90%.